The Intersection of Crime Seriousness, Discretion, and Race: A Test of the Liberation Hypothesis. (2nd January 2017) - Hauser, William; Peck, Jennifer H.
Abstract : Spohn and Cederblom's interpretation of the liberation hypothesis asserts that with trivial crimes, judges are "liberated" to consider extra-legal attributes such as race when making sentencing decisions. The current study posits that this perspective may be too theoretically simplistic because it fails to distinguish between the concepts of discretion and uncertainty. In light of this argument, we examine the sentencing decisions of felony cases in the Florida circuit courts. Results indicate that blacks and Hispanics are more likely to be imprisoned than whites, and males more so than females. Contrary to expectations, this disparity increases with crime seriousness. Consistent with the imprisonment model, blacks and males receive longer sentences and the effect increases with case seriousness. We found no evidence that the effect of offender extra-legal attributes depends upon the characteristics of the judges handling the cases. Suggestions for future research and implications for the liberation hypothesis are discussed.